2021
DOI: 10.3389/fonc.2021.702491
|View full text |Cite
|
Sign up to set email alerts
|

YBX1 Enhances Metastasis and Stemness by Transcriptionally Regulating MUC1 in Lung Adenocarcinoma

Abstract: Abnormal expression of the transcription factor Y-box-binding protein-1 (YBX1) is associated with the proliferation, migration, aggressiveness, and stem-like properties of various cancers. These characteristics contribute to the tumorigenesis and metastasis of cancer. We found that the expression levels of Mucin-1 (MUC1) and YBX1 were positively correlated in lung adenocarcinoma cells and lung adenocarcinoma tissue. Our retrospective cohort study of 176 lung adenocarcinoma patients after surgery showed that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…In melanoma, YB-1 promotes a highly invasive phenotype [ 60 ]. Additionally, YB-1 promotes the metastasis of liver cancer [ 61 ], gastric cancer [ 58 ], skin squamous cell carcinoma [ 62 ], spinal chordoma [ 46 ], ovarian cancer [ 63 ], prostate cancer [ 64 ], and lung adenocarcinoma [ 65 ]. Interestingly, one study showed that human YB-1 inhibited AKT-dependent oncogenic transformation in NIH3T3 [ 66 ].…”
Section: The Functions and Mechanisms Of Yb-1mentioning
confidence: 99%
“…In melanoma, YB-1 promotes a highly invasive phenotype [ 60 ]. Additionally, YB-1 promotes the metastasis of liver cancer [ 61 ], gastric cancer [ 58 ], skin squamous cell carcinoma [ 62 ], spinal chordoma [ 46 ], ovarian cancer [ 63 ], prostate cancer [ 64 ], and lung adenocarcinoma [ 65 ]. Interestingly, one study showed that human YB-1 inhibited AKT-dependent oncogenic transformation in NIH3T3 [ 66 ].…”
Section: The Functions and Mechanisms Of Yb-1mentioning
confidence: 99%
“…IGF2BP1 stabilized the YBX1 by correlating with the Coding Region instability Determinant (CRD) 26 . Moreover, YBX1 was upregulated in lung adenocarcinoma and acted as an independent predictor of the prognosis and recurrence of lung adenocarcinoma 27 . The stabilization of YBX1 by IGF2BP1 may be a crucial mechanism in the onset and progression of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…The same number of cells (1000) were seeded into ultra‐low attachment culture dishes and cultured in RMPI‐1640 supplemented with 2% B27 (Thermo Fisher, USA), 20 ng/mL epidermal growth factor, and 10 ng/mL basic fibroblast growth factor (BD, USA) in 10% FBS for 10 days. Cell balls were observed with an inverted microscope and photographed, and the longest diameter was calculated by the scale size in the images using Image‐Pro Plus software 16 …”
Section: Methodsmentioning
confidence: 99%